Peran Mahasiswa pada Kegiatan Asistensi Mengajar dalam Memotivasi Siswa SMKN 01 Dompu dan SMPN 04 Dompu untuk Berwirausaha - Nafisah Nurulrahmatiah; Ita Purnama; Rosa Dwiyanti; Efan Iriadi; Andini Ramadani (Institut Nalanda, 2024)
This study uses a case study of SMKN 01 Dompu and SMPN 04 Dompu to provide a teaching assistance role in encouraging students of SMKN 01 Dompu and SMPN 04 Dompu to be entrepreneurial. Entrepreneurial skills are one of the important skills that must be learned early in the era of increasingly competitive globalization. Students have opportunity to learn directly from teachers through teaching assistant programs, which focus on entrepreneurial skills such as decision-making, risk management, and creativity. This study found that teaching assistants at SMKN 01 Dompu and SMPN 04 Dompu can encourage students to think more creatively and innovatively. This was found through observation and interview methods. The program also boosts students' confidence in starting a small business. The results of the study show that teachers who are actively involved in teaching assistance programs can make education fun and relevant, thereby fostering students' interest in exploring the world of entrepreneurship.